The future digital workplace: a review - Mohd Razali, Masliza; Mohd Nor, Khalijah; Bashirun, Siti Norashikin (GADING Journal for the Social Sciences, 2024)
As a dynamic and transformative idea in the field of work and organizational administration, the "digital workplace" has attracted growing interest. This review integrates findings from a substantial body of research published between 2014 and 2023, gathered from reliable databases like SCOPUS, to provide a thorough overview of the development, essential elements, technological underpinnings, advantages, challenges, and adaptation of the digital workplace. This study explores how the digital workplace evolved into not only a strategic option but also a requirement for business continuity in light of the global COVID-19 that developed throughout the review period. It offers useful insights for organisations and researchers looking to leverage the digital workplace to improve agility, productivity, and resilience in an ever-changing digital context.